Temporal changes in cortical oxygenation in the motor-related areas and bilateral prefrontal cortex based on exercise intensity and respiratory metabolism during incremental exercise in male subjects: A near-Infrared spectroscopy study - Kojima, Sho; Morishita, Shinichiro; Hotta, Kazuki; Qin, Weixiang; Usui, Naoto; Tsubaki, Atsuhiro (Frontiers in Physiology, 2022)
A recent study has reported that prefrontal cortex (PFC) activity during incremental exercise may be related to exercise termination on exhaustion. However, few studies have focused on motor-related areas during incremental exercise. This study investigated changes in the oxygenation of the PFC and the motor-related area during incremental exercise, which was measured by near-infrared spectroscopy, and analyzed the effect of exercise termination on changes in cortical oxygenation based on exercise intensity and respiratory metabolism. Sixteen healthy young male patients participated in this study. After a 4-min rest and 4-min warm-up period, incremental exercise was started at an incremental load corresponding to 20 W/min. Oxyhemoglobin (O2Hb), deoxyhemoglobin (HHb), and total hemoglobin (THb) in the bilateral PFC, supplementary motor area, and primary motor cortex were measured. We evaluated changes in oxygenation in each cortex before and after the anaerobic threshold (AT) and respiratory compensation point to identify changes due to respiratory metabolism. O2Hb and THb increased from moderate intensity or after AT to maximal exercise, and HHb increased slowly compared to O2Hb and THb; these changes in hemoglobin levels were consistent in all cortical areas we measured. However, the increase in each hemoglobin level in the bilateral PFC during incremental exercise was faster than that in motor-related areas. Moreover, changes in cortical oxygenation in the right PFC were faster than those in the left PFC. These results suggest changes based on differences in neural activity due to the cortical area.